Implications of Movement Limitation During the 1965-1966 Tragedy on Indonesian Exiles Citizenship Rights - Wahyu Nugroho; Lukman Khakim; Kyra Tasanee Alifah (UIN Sunan Kalijaga Yogyakarta, 2024)
The political turmoil that occurred in 1965-1966 led the government at that time to impose limitation in freedom of movement with the aim of maintaining security and public order. However, these limitation affected the citizenship status of the Indonesian diaspora. This research aims to analyze and elaborate on the extent to which limitations on freedom of movement in the 1965–1966 tragedy can have implications for the citizenship rights of the Indonesian diaspora. The analysis of these problems is carried out through normative legal research methods with a conceptual approach. The results show that the substance of limitation in freedom of movement in international human rights instruments requires clarity on the purpose of limitation and the principle of proportionality and does not negate rights. This contrasts with the limitations on freedom of movement in the 1965–1966 tragedy, which were carried out disproportionately. As a result, many Indonesian diasporas at that time lost their citizenship status and its rights. Those who lost their citizenship status were then referred to as Indonesian exiles.